Legochnaya arterial'naya gipertenziya: na puti ot ratsional'noy diagnostiki k vyboru effektivnoy lekarstvennoy terapii - I E Chazova; T V Martynyuk (Системные гипертензии, 2013)
Pulmonary arterial hypertension (PAH) is a clinical condition characterized by precapillary pulmonary hypertension (PH) in the absence of other causes leading to an increase of blood pressure in the pulmonary artery (PA), such as lung diseases, chronic PA thromboembolism, etc., including rare diseases. The Fourth World Symposium on PH in 2008 proposed new diagnostic criteria for PAH: a resting mean PA pressure ≥25 mm Hg with a normal PA wedge pressure ≤15 mmHg. PAH is the first category of PH involving different nosological entities with similar clinical manifestations, morphological patterns, and hemodynamic disorders. The key component in the pathogenesis of PAH is endothelial dysfunction with imbalance between vasodilators and vasoconstrictors and activation of the blood coagulation system, giving rise to pulmonary vascular remodeling and enhanced pulmonary vascular resistance. The detection of potential targets for therapeutic exposure and a considerable number of randomized trials using the pathogenic therapeutic agents led to the introduction of medicines that affect three potential targets: 1) deficiency of prostacyclin that replenishes its analogues (prostanoids); 2) that of nitric oxide, the vasodilator effect of which is associated with the elevated level of cyclic guanosine monophosphate, which substantially improved treatment possibilities in patients with PAH. The PACES trial of the efficacy of sildenafil in combination with intravenous epoprostenol is an example of effective specific combination therapy for PAH.